Machine vision inspection systems. Volume 1, Image Processing, Concepts, Methodologies and Applications - Malarvel, Muthukumaran; Nayak, Soumya Ranjan, 1984-; Panda, Sury Narayan; Pattnaik, Prasant Kumar, 1969-; Muangnak, Nittaya (Hoboken, NJ : Wiley-Scrivener, 2020)
"Machine Vision Inspection Systems (MVIS) is a multidisciplinary research field that emphasizes the image processing, machine vision and pattern recognition for industrial applications. Inspection techniques are generally used in destructive and non-destructive evaluation industry. Recently, the current automated vision research on machine inspection has gained more popularity with researchers and engineers, because the manual assessment of the inspection may fail and turn into false assessment due to a large number of examinations during the inspection process, leading to potential disaster. Machine Vision Inspection Systems (MVIS) is better able to avoid false assessment"--
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Computer vision; Computer vision -- Industrial applications; Engineering inspection -- Automation; Image processing; Image processing -- Digital techniques; Vision par ordinateur; Vision par ordinateur -- Applications industrielles; x; Traitement d'images.; Traitement d'images; image processing; digital imaging; Computer vision; Computer vision -- Industrial applications; Engineering inspection -- Automation; Image processing; Image processing -- Digital techniques